Getting athletes back in the game - Denis Arsovski; Erblin Domazeti; Tanja Jovanovska; Gordana Ristevska-Dimitrovska (University of Applied Sciences in Tarnow, Poland, 2023)
Movement is an essential characteristic that has developed over the course of human evolution. With the inclusion of various populations in sports activities, sports have become an important part of people's daily lives. Knee injuries are common among athletes, with knee joint being the most vulnerable to various injuries. Knee injuries require appropriate treatment to allow the athlete to return to their sports activities. Additionally, this study aimed to increase awareness of the importance of preventing knee injuries in sports and to highlight the potential impact of such injuries on an athlete's ability to participate in their sport. A cross-sectional study was conducted to evaluate the functional outcomes of athletes with knee injuries. The study included 38 patients with knee injuries (ACL, meniscal injuries, collateral ligament injuries) out of which 21 were physically active athletes, 9 were not, but they were athletes who were not involved in sports at the time of the testing and 8 were recreational athletes. The majority of respondents (76%) reported that they sustained the injury during sports activities. Knee pain was reported as at least once a week by most respondents. The study highlights the importance of proper knee injury prevention measures during sports activities and the need for prompt and effective rehabilitation for those who do suffer injuries. Overall, these findings have important implications for the treatment and management of knee injuries among athletes and individuals seeking to maintain an active lifestyle.